Fuzzy databases [electronic resource] : modeling, design and implementation - Galindo, Jose , 1970-; Piattini, Mario , 1966-; Urrutia, Angelica (Idea Group Pub., 2006)
"This book includes an introduction to fuzzy logic, fuzzy databases and an overview of the state of the art in fuzzy modeling in databases"--Provided by publisher